Coastal Freshening Prevents Fjord Bottom Water Renewal in Northeast Greenland: A Mooring Study From 2003 to 2015 - Wieter Boone; Søren Rysgaard; Daniel F. Carlson; Lorenz Meire; Sergei Kirillov; John Mortensen; Igor Dmitrenko; Leendert Vergeynst; Mikael K. Sejr (Geophysical Research Letters)
Abstract The freshwater content of the Arctic Ocean and its bordering seas has recently increased. Observing freshening events is an important step toward identifying the drivers and understanding the effects of freshening on ocean circulation and marine ecosystems. Here we present a 13 year (2003–2015) record of temperature and salinity in Young Sound‐Tyrolerfjord (74°N) in Northeast Greenland. Our observations show that strong freshening occurred from August 2005 to August 2007 (−0.92 psu or −0.46 psu yr−1) and from August 2009 to August 2013 (−0.66 psu or −0.17 psu yr−1). Furthermore, temperature‐salinity analysis from 2004 to 2014 shows that freshening of the coastal water (~range at sill depth: 33.3 psu in 2005 to 31.4 psu in 2007) prevented renewal of the fjord's bottom water. These data provide critical observations of interannual freshening rates in a remote fjord in Greenland and in the adjacent coastal waters and show that coastal freshening impacts the fjord hydrography, which may impact the ecosystem dynamics in the long term.